The reflective diary experiences of EFL pre-service teachers. Issue 2 (4th March 2021) - Altalhab, Sultan; Alsuhaibani, Yasser; Gillies, Donald
ABSTRACT: This study investigated the use of reflective diaries by novice teachers in the teaching practicum course. In these diaries, novice teachers wrote about the activities they had undertaken during the week in detail. These novice teachers were also interviewed in order to garner rich, in-depth, and nuanced perceptions of their experiences in writing reflective diaries and ascertain whether the diaries helped or hindered their teaching. Fifty Saudi pre-service teachers who taught English in intermediate schools participated in the study. The in-service teachers in these schools were interviewed so that their voices and evaluations regarding the reflective diaries could be added to the study; this was done because they were considered as secondary supervisors for the pre-service teachers. Results revealed that the majority of pre-service teachers and all of the in-service teachers showed positive attitudes toward reflective diary use. Although most of the diaries were descriptive rather than reflective, the pre-service teachers did focus on key classroom elements such as teaching techniques, activities, teaching resources. The results also suggested that a number of participants recommended that the diaries should be mandatory and embedded in the teaching practicum course. Dedicated coaching, mentoring, and modelling could further develop their approach to professional reflection.